2009
DOI: 10.1017/s0007114509382148
|View full text |Cite
|
Sign up to set email alerts
|

Effects of red grape juice polyphenols in NADPH oxidase subunit expression in human neutrophils and mononuclear blood cells

Abstract: The NADPH oxidase enzyme system is the main source of superoxide anions in phagocytic and vascular cells. NADPH oxidase-dependent superoxide generation has been found to be abnormally enhanced in several chronic diseases. Evidence is accumulating that polyphenols may have the potential to improve cardiovascular health, although the mechanism is not fully established. Consumption of concentrated red grape juice, rich in polyphenols, has been recently shown to reduce NADPH oxidase activity in circulating neutrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 56 publications
3
22
0
3
Order By: Relevance
“…The NF-κB pathway augments pro-survival signaling by activating PI3K/AKT/ERK1/2 pathways and ultimately leads to the phosphorylation inactivation of proapoptotic proteins such as Bid and Bax and upregulation of anti-apoptotic genes such as Bcl-2 and Bcl-X L (McCubrey et al, 2007). The Nox-dependent superoxide generation has been found to be abnormally enhanced in several chronic diseases including cancer (Davalos et al, 2009). We found that midazolam inhibits the enzyme activity of Nox2 subunits in K562 cells (Fig.…”
Section: +mentioning
confidence: 99%
“…The NF-κB pathway augments pro-survival signaling by activating PI3K/AKT/ERK1/2 pathways and ultimately leads to the phosphorylation inactivation of proapoptotic proteins such as Bid and Bax and upregulation of anti-apoptotic genes such as Bcl-2 and Bcl-X L (McCubrey et al, 2007). The Nox-dependent superoxide generation has been found to be abnormally enhanced in several chronic diseases including cancer (Davalos et al, 2009). We found that midazolam inhibits the enzyme activity of Nox2 subunits in K562 cells (Fig.…”
Section: +mentioning
confidence: 99%
“…Furthermore, polyphenols from grape extracts, sometimes with a high content of procyanidins, have been demonstrated to reduce NADPH oxidase subunit expression in human neutrophil mononuclear cells and in an endothelial cell line [Davalos et al, 2009]; and at the left ventricle in a model of highfructose-fed rats [Al-Awwadi et al, 2005] and in an obese hamster model [Decorde et al, 2009]. These effects on NADPH oxidase expression could have contributed to the direct NADPH oxidase inhibitory activity observed in our in vivo treatments of grape procyanidins.…”
Section: Discussionmentioning
confidence: 84%
“…NADPH oxidase-dependent superoxide generation has been found to be abnormally enhanced in several chronic diseases (40). However, extensive analysis of the expression of NADPH oxidase subunits, particularly two critical subunits gp91 phox and p22 phox , in breast cancer cells and their regulation in lipid rafts has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%